GÖRSEL PROGRAMLAMA ORTAMLARINDA YAPILAN OYUN GELİŞTİRME ETKİNLİKLERİNİN ETKİLİLİĞİ. - BALCI, Hasan; KORKMAZ, Özgen; ÇAKIR, Recep; UĞUR ERDOĞMUŞ, Feray (Mehmet Akif Ersoy University Journal of Education Faculty, 2021)
The aim of this study is to reveal the effects of game development activities of primary school students on visual programming tools on students' attitudes towards programming, selfsufficiency perceptions and students' views on coding. In this research, mixed research method was used. Quantitive data were used with the pretestposttest control group quasi-experimental research design. Qualitative data were used with case study. The study group was determined using the easy sampling method from a primary school in Amasya. "Computer Programming Learning Attitudes Scale" and "Self-sufficiency Perception Scale for Scratch Program" were used as pre-test and post-test for both groups. In addition, an interview form was prepared and applied to the students. As a result of the analysis, there was not a significant difference in the post-test of students' programming towards game programming activities in visual programming environments. Similarly, there was no significant difference between self-sufficiency perceptions of students. Although there was no significant difference, when the qualitative data were analyzed, it was seen that students had an interest in visual programming and their motivation was high.